2019
DOI: 10.1002/celc.201900202
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Pinacol Coupling of Acetophenone Using Boron‐Doped Diamond Electrode

Abstract: An electrochemical pinacol coupling reaction of acetophenone using a boron‐doped diamond (BDD) electrode has been reported. This transformation is driven by the one‐electron reduction of acetophenone on the BDD cathode, followed by an intermolecular radical coupling. Owing to the BDD's outstanding electrochemical properties, the pinacol‐type compound has been obtained in good conversion yield. The roles of a supporting electrolyte and solvent were addressed; (1) lithium ions contribute to increase in the react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 54 publications
(21 reference statements)
0
14
0
Order By: Relevance
“…The Yamamoto group recently reported an electrochemical pinacol coupling of ketones using boron-doped diamond (BDD) as the electrode. 63 However, low conversion yields (10−79%) were obtained, which might be due to the lack of effective adsorption of aryl rings on the BDD surface. These results suggested that the adsorption of the aryl ring was favorable to the formation of pinacol 2a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Yamamoto group recently reported an electrochemical pinacol coupling of ketones using boron-doped diamond (BDD) as the electrode. 63 However, low conversion yields (10−79%) were obtained, which might be due to the lack of effective adsorption of aryl rings on the BDD surface. These results suggested that the adsorption of the aryl ring was favorable to the formation of pinacol 2a.…”
Section: Resultsmentioning
confidence: 99%
“…This result further confirmed the importance of the adsorption of the aryl ring in this electrochemical pinacol coupling. The Yamamoto group recently reported an electrochemical pinacol coupling of ketones using boron-doped diamond (BDD) as the electrode . However, low conversion yields (10–79%) were obtained, which might be due to the lack of effective adsorption of aryl rings on the BDD surface.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the C–O ether cleavage on the skeletal Ni electrode surface is qualitatively different from the electron transfer process. Meanwhile, as reported by Yamamoto and co-workers, carbon electrodes are capable of electron transfer to the benzylic ketone of acetophenone, leading to pinacol coupling of two ketyl radicals to generate 2,3-diphenylbutane-2,3-diol as the stereoisomers …”
Section: Resultsmentioning
confidence: 85%
“…Meanwhile, as reported by Yamamoto and co-workers, carbon electrodes are capable of electron transfer to the benzylic ketone of acetophenone, leading to pinacol coupling of two ketyl radicals to generate 2,3-diphenylbutane-2,3-diol as the stereoisomers. 42 With the RVC at high current, the amount of acetophenone dropped quickly within 1 h of cathodic treatment (see S30). After 9 h of reduction, only about 21% of 1-phenylethanol was observed (Table 1, Entry 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation